2020
DOI: 10.1002/jpen.1966
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and Other Nutrition Assessment Methods to Monitor the Nutrition Status of Critically Ill Patients

Abstract: Background This study aims to evaluate the use of ultrasonography (US) as an instrument to assess the quadriceps muscles in patients admitted to intensive care units (ICUs), comparing the evolution of US‐assessed mass muscle to other nutrition methods. Methods We conducted a prospective observational study of adult patients aged ≥18 years admitted to an ICU of the Hospital das Clínicas in Brazil. Quadriceps muscle measurements were performed by US, and adductor pollicis muscle thickness and arm, calf, and thig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 25 publications
4
32
1
15
Order By: Relevance
“…In agreement with our results, Rodrigues et al [18] found reductions in quadriceps thickness and rectus femoris cross-sectional area. Muscle mass loss by anthropometric measurements was similar between nourished and malnourished individuals.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our results, Rodrigues et al [18] found reductions in quadriceps thickness and rectus femoris cross-sectional area. Muscle mass loss by anthropometric measurements was similar between nourished and malnourished individuals.…”
Section: Discussionsupporting
confidence: 94%
“…8 These elements, which are needed for a proper interpretation of the ICCs, have commonly been missing in general medical literature. Table 1 summarizes the elements reported in the five papers published in the Journal of Parenteral and Enteral Nutrition [1][2][3][4][5] regarding a particular topic, the reliability of muscle mass measurements by different methods. Note that only one study reported, in the methods and/or results, all necessary elements for a proper interpretation of the ICCs or a strategy for choosing.…”
Section: Intraclass Correlation Coefficient and Reliability Of Muscle Mass Measurementsmentioning
confidence: 99%
“…In the last year, five papers that reported intraclass correlation coefficients (ICCs) for the reliability of muscle mass measurements were published in the Journal of Parenteral and Enteral Nutrition. [1][2][3][4][5] the degree of correlation and agreement between different measurements and is subject to a variety of statistical assumptions, violations of which may lead to inflated estimates. 6 Based on three different models (one-way random effects, two-way random effects, and two-way mixed effects), two types of measurements (single or average measures), and two output definitions (consistency or absolute agreement), there are, by convention, 10 types of ICCs 7 differentially used for various purposes, such as repeatability and reliability.…”
Section: E T T E R T O T H E E D I T O R Intraclass Correlation Coefficient and Reliability Of Muscle Mass Measurementsmentioning
confidence: 99%
“…It can be performed serially and detect short-term changes. A prospective study by Rodrigues et al 27 assessed quadriceps and rectus femoris muscle thickness using ultrasonography and the reduction in muscle mass was correlated with severe malnutrition. Ultrasonographic assessment of muscle mass needs further validation and is a useful future tool.…”
Section: N Utritional R Isk S mentioning
confidence: 99%